2012
DOI: 10.2460/ajvr.73.12.1859
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of body surface area via computed tomography–guided modeling in domestic rabbits (Oryctolagus cuniculus)

Abstract: Objective To optimize the use of CT-guided modeling for the calculation of body surface area (BSA) in domestic rabbits (Oryctolagus cuniculus). Animals 12 domestic rabbits. Procedures Adult rabbits (body weight, 1 to > 4 kg) that were client-owned animals undergoing CT for disease diagnosis or deceased laboratory animals donated from other research projects were scanned with a CT scanner. Images were transferred to a radiation therapy planning software program. Image slices were captured as contiguous slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…The present k value was larger than the k value (9.9) of rabbits (NZW, Mini-lop, Netherland Dwarf, Dutch Belted, Chinchilla, Flemish Giant, and breed unknown) analyzed the CT images using their own procedure reported by Zehnder [ 15 ]. The surface area of the small cuboid was computed to be 0.111 ± 0.001 m 2 (mean ± SD) from the MPR of CT images by Zehnder’s procedure (i.e., summing the lengths of contour for each slice and multiplying this total length by the reconstruction interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present k value was larger than the k value (9.9) of rabbits (NZW, Mini-lop, Netherland Dwarf, Dutch Belted, Chinchilla, Flemish Giant, and breed unknown) analyzed the CT images using their own procedure reported by Zehnder [ 15 ]. The surface area of the small cuboid was computed to be 0.111 ± 0.001 m 2 (mean ± SD) from the MPR of CT images by Zehnder’s procedure (i.e., summing the lengths of contour for each slice and multiplying this total length by the reconstruction interval.…”
Section: Discussionmentioning
confidence: 99%
“…The surface area of the small cuboid was computed to be 0.111 ± 0.001 m 2 (mean ± SD) from the MPR of CT images by Zehnder’s procedure (i.e., summing the lengths of contour for each slice and multiplying this total length by the reconstruction interval. Additionally, the areas of the end slices were added to this value [ 15 ]). The average value computed by Zehnder’s procedure was 80.4% of the calculated value (0.138 m 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography (CT) modeling has been used to formulate a K constant in rabbits. In that study, CT images from 12 pet rabbits were transferred to radiation therapy planning software and 1 mm slices were used to generate the surface contours to determine BSA, and nonlinear regression was then used in the current formula to generate a K constant of 9.9 . This was similar to another CT‐based derivation of a BSA formula for ferrets which yielded a K constant of 9.94 with the help of 3D surface modeling using open‐source imaging software to determine BSA .…”
Section: Introductionmentioning
confidence: 99%
“…The k values (100 × BSA [m 2 ] = k × BW [kg] 2/3 , i.e., Meeh’s formula) for various animal species have been reported and used to extrapolate the test results between species. To date, the k values for rabbits have been calculated in various ways; k values of 5.7 to 10.0 were determined by use of skinning and triangulation reported by Spector [16], while values of 12.0 to 12.9 were reported by Fougère and Wynn who did not show the method of BSA determination [4], and Zehnder et al reported a k value of 9.9 analyzed the Computed tomography (CT) images using their own procedure [17]. Additionally, Bai et al reported 7-month old male JW (working BW range: 2.5 to 3.0 kg) k values of 11.30 to 11.35 determined by use of paper cover and skinning [1].…”
Section: Introductionmentioning
confidence: 99%